Excess mortality associated with elevated body weight in the USA by state and demographic subgroup: A modelling study. (June 2022) - Ward, Zachary J.; Willett, Walter C.; Hu, Frank B.; Pacheco, Lorena S.; Long, Michael W.; Gortmaker, Steven L.
Summary: Background: The obesity epidemic in the USA continues to grow nationwide. Although excess weight-related mortality has been studied in general, less is known about how it varies by demographic subgroup within the USA. In this study we estimated excess mortality associated with elevated body weight nationally and by state and subgroup. Methods: We developed a nationally-representative microsimulation (individual-level) model of US adults between 1999 and 2016, based on risk factor data from 6, 002, 012 Behavioral Risk Factor Surveillance System respondents. Prior probability distributions for hazard ratios relating body-mass index (BMI) to mortality were informed by a global pooling dataset. Individual-level mortality risks were modelled accounting for demographics, smoking history, and BMI adjusted for self-report bias. We calibrated the model to empirical all-cause mortality rates from CDC WONDER by state and subgroup, and assessed the predictive accuracy of the model using a random sample of data withheld from model fitting. We simulated counterfactual scenarios to estimate excess mortality attributable to different levels of excess weight and smoking history. Findings: We estimated that excess weight was responsible for more than 1300 excess deaths per day (nearly 500, 000 per year) and a loss in life expectancy of nearly 2·4 years in 2016, contributing to higher excess mortality than smoking. Relative excess mortality rates were nearly twice as high for women compared to men in 2016 (21·9% vs 13·9%), and were higher for Black non-Hispanic adults. By state, overall excess weight-related life expectancy loss ranged from 1·75 years (95% UI 1·57–1·94) in Colorado to 3·18 years (95% UI 2·86-3·51) in Mississippi. Interpretation: Excess weight has substantial impacts on mortality in the USA, with large disparities by state and subgroup. Premature mortality will likely increase as obesity continues to rise. Funding: The JPB Foundation, NIH, CDC